Some factors attracting new arrivals in the urban fringe areas: A Case Study of Sinduadi, Mlati, Sleman, Yogyakarta, Indonesia - Hadi Sabari Yunus (Faculty of Geography, Universitas Gadjah Mada, 1991)
In the discussion on any urban development, one can not neglect the so=called centrifugal and centripetal forces causing the flow of either people and functions from and to the inner parts of the city or the fringe. These two forces constitute the dynamic doers for the development of the city concerned. One of the aspects of urban development is a change in physical performance of the city itself and the sprawling process of urban features in the surrounding countrysides. The study is carried out in one of the portions of the fringe areas of the city of Yogyakarta that is receiving many arrivals either from the inner parts of the city or from the more remotely located areas. The discussion is merely focussed on one of these broad scopes, i.e., movement of people either coming from the inner parts of the city and coming from the more remotely located hinterlands. One of the subdistricts located next to the municipal boundaries is chosen as a case study and the respondents are selected randomly among new migrants in the last ten years. The result shows that nine reasons constitute attracting factors to the fringe areas. Centrifugal movement is predominated by those who are looking for more spacious placelspace for living and the lower price of laud whereas centripetal movement is predominated by those who are approaching their place of work.